Pertumbuhan Perusahaan sebagai Pemoderasi Pengaruh Leverage pada Nilai Perusahaan - Ambri, Debbi Devinta; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p17, 2018)
This study aims to obtain empirical evidence of company growth as a moderator of the effect of leverage on the value of automotive companies and components listed on the Indonesia Stock Exchange in the period 2014-2016. Sampling method used is purposive sampling. The number of companies that meet the criteria is 12 companies with the number of 36 observers. Data collection was done by non participant observation method. Data analysis technique used is test of Moderated Regression Analysis (MRA). Based on the result of research, it is known that leverage have negative effect on firm value. The study also found that firm growth was able to strengthen the leverage effect on corporate value. This shows the high low growth ratio of the company and immediately affect the value of the company. Keywords: Firm Value, Leverage, Company Growth